Toward an Anti-Inflammatory Strategy for Depression - Hayley, Shawn (Frontiers in Behavioral Neuroscience, 2011)
It has become clear that the inflammatory immune system is altered during the course of clinical depression. In particular, the human data have found depression to be associated with disturbances in the trafficking of cells of the adaptive immune system, coupled with elevations of innate immune messengers and pro-inflammatory cytokines. Paralleling these findings, stressor-based animal models of depression have implicated several cytokines, most notably interelukin-1β (IL-1β), IL-6 and tumor necrosis factor-α (TNF-α). Elevations of these cytokines and general inflammatory indicators, such as C-reactive protein, together with reductions of specific immune cells (e.g. T lymphocytes) might serve as useful biomarkers of depression or at least, certain subtypes of the disorder. Recent reports also suggest the possibility that anti-inflammatory agents could have therapeutic value in acting as adjunct treatments with traditional antidepressants. Along these lines, we presently discuss the evidence for pro-inflammatory cytokine involvement in depression, as well as the possibility that anti-inflammatory agents and trophic cytokines themselves might have important anti-depressant properties.